The Effects of Boron on Arsenic‐Induced Lipid Peroxidation and Antioxidant Status in Male and Female Rats. Issue 12 (16th July 2015) - Kucukkurt, Ismail; Ince, Sinan; Demirel, Hasan Huseyin; Turkmen, Ruhi; Akbel, Erten; Celik, Yasemin
ABSTRACT: The aim of the present study was to investigate the possible protective effects of boron, an antioxidant agent, against arsenic‐induced oxidative stress in male and female rats. In total, 42 Wistar albino male and female rats were divided into three equal groups: The animals in the control group were given normal drinking water, the second group was given drinking water with 100 mg/L arsenic, and the third group was orally administered drinking water with 100 mg/kg boron together with arsenic. At the end of the 28‐day experiment, arsenic increased lipid peroxidation and damage in the tissues of rats. However, boron treatment reversed this arsenic‐induced lipid peroxidation and activities of antioxidant enzymes in rats. Moreover, boron exhibited a protective action against arsenic‐induced histopathological changes in the tissues of rats. In conclusion, boron was found to be effective in protecting rats against arsenic‐induced lipid peroxidation by enhancing antioxidant defense mechanisms.